The distal location of the iron responsive region of the hepcidin promoter - Truksa, Jaroslav (American Society of Hematology, 2007)
The response of hepcidin transcription to iron has been repeatedly documented in living mice, but it is difficult to demonstrate the response in ex vivo systems. We have hydrodynamically transfected mice with plasmid constructs composed of a murine hepcidin 1 promoter and fragments of the promoter fused to a firefly luciferase reporter. This method enabled us to quantitate the response of the hepcidin promoter to short-term feeding of a high-iron diet to mice that have been maintained on an iron-deficient diet. We show that the region of the promoter between 1.6 Kb and 1.8 Kb upstream from the start of translation is essential for the response to iron. The promoter region between −260 bp and −1.6 Kb is not essential for the iron responsiveness of hepcidin promoter. The iron-responsive region that we have mapped is the same region required for the in vitro response of HepG2 cells to stimulation with bone morphogenetic proteins and differs from the LPS/IL-6 responsive area.